2014
DOI: 10.1074/jbc.m114.583591
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Protein Nef Inhibits Activity of ATP-binding Cassette Transporter A1 by Targeting Endoplasmic Reticulum Chaperone Calnexin

Abstract: Background: HIV-1 Nef inhibits activity of ABCA1 and suppresses cholesterol efflux. Results: Nef binds to calnexin and disrupts its interaction with ABCA1 but enhances calnexin interaction with viral gp160. Conclusion: Nef regulates activity of calnexin to favor maturation of HIV gp160 at the expense of ABCA1. Significance: Learning how Nef regulates activity of calnexin is crucial for designing therapeutic strategies aimed at treating HIV infection and HIV-associated atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 47 publications
(40 reference statements)
5
37
0
Order By: Relevance
“…Importantly, ABCC7 and ABCB1 mutants that escape CNX binding do not achieve mature glycosylation and these mutations result in reduced transporter function 8, 9 . Our recently published study demonstrated that ABCA1 interacts with CNX, and reduction of CNX expression by RNAi resulted in a significant decrease in functional activity of ABCA1, evidenced by reduced cholesterol efflux to ABCA1-specific acceptor apoA-I 5 . We also showed that Nef impairs interaction between ABCA1 and CNX, and this effect of Nef is essential for inactivation and downregulation of ABCA1 5 .…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Importantly, ABCC7 and ABCB1 mutants that escape CNX binding do not achieve mature glycosylation and these mutations result in reduced transporter function 8, 9 . Our recently published study demonstrated that ABCA1 interacts with CNX, and reduction of CNX expression by RNAi resulted in a significant decrease in functional activity of ABCA1, evidenced by reduced cholesterol efflux to ABCA1-specific acceptor apoA-I 5 . We also showed that Nef impairs interaction between ABCA1 and CNX, and this effect of Nef is essential for inactivation and downregulation of ABCA1 5 .…”
Section: Introductionmentioning
confidence: 93%
“…Our recently published study demonstrated that ABCA1 interacts with CNX, and reduction of CNX expression by RNAi resulted in a significant decrease in functional activity of ABCA1, evidenced by reduced cholesterol efflux to ABCA1-specific acceptor apoA-I 5 . We also showed that Nef impairs interaction between ABCA1 and CNX, and this effect of Nef is essential for inactivation and downregulation of ABCA1 5 . Importantly, inhibition of ABCA1-CNX interaction by Nef is specific, as interaction between ABCA1 and two other proteins, dystrophin and serine palmitoyltransferase, shown previously to bind ABCA1 10 , was not affected.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…6,7 However, the only in vivo evidence for the effects of Nef on cholesterol metabolism are studies where recombinant Nef was injected into mice. 8 These studies demonstrated an enhanced development of atherosclerosis in a mouse model of this disease (apoe -/-mice on high fat diet), and in wild-type C57BL/6 mice fed high-fat/high-cholesterol diet, Nef induced accumulation of lipid-laden macrophages in adventitia of aorta.…”
mentioning
confidence: 99%
“…Future studies would also be required to determine the chain of molecular events behind the Nef-induced accumulation of lipid droplets. Nef is known to impair the function of the ABCA1 cholesterol transporter, 6 but may also, through its association with calnexin, 7 affect other proteins involved in lipid synthesis or transport. Nef interaction with Acyl-CoA thioesterase 8 (ACOT8) 15,16 may also influence fatty acid metabolism.…”
mentioning
confidence: 99%